Implementasi Kebijakan Desa Antikorupsi di Kalurahan Karangsewu Kulon Progo - Sumaryati, Sumaryati (Pancasila and Civics Education Journal (PCEJ), 2024)
In 2022 there were 133 cases of village fund corruption out of 155. Weakintegrity is the cause. Strengthening the integrity of village government officials with the anti-corruption village program. This program contributes to the prevention of corruption, but many village governments do not know about it. The vision and mission of Karangsewu village is in line with this program. The purpose of the study was to determine the implementation of the anti-corruption village aspect in Karangsewu village and its obstacles. Data collection using interviews and documentation. Data analysis techniques with reduction, classification, data display, conclusion. The results of the research show that each program refers to Perkal, Pergub, and or Perbub, supervision is carried out with a finger print system, dukuh work boxes, routine coordination meetings once a month. Community service through Pukesos and social media (kalurahan web, WAGrup). Community involvement with musduk, muskal, and musrenbangkal. The local wisdom of merti dusun has implemented anti-corruption values although it has not been programmed. Constraints are the lack of Perkal to support policy implementation, BPKal time management is not proportional, participation is still measured by attendance at activities, and there is no specific local wisdom related to anti-corruption.